Efficacy and tolerability of a combined gatifloxacin plus prednisolone formulation for topical prophylaxis after LASIK - Mauro Campos (Dove Medical Press, 2011)
Mauro Campos, Cristina Muccioli, João BNS Malta, Rafael A Gerade, André LA Salame, Rubens Belfort JrDepartment of Ophthalmology, Hospital São Paulo, Universidade Federal de São Paulo, BrazilPurpose: To compare the efficacy and tolerability of a fixed-dose combination of 0.3% gatifloxacin and 1% prednisolone formulation versus the same agents administered separately for prophylaxis in a laser-assisted in situ keratomileusis (LASIK) population.Methods: In a prospective, randomized, double-masked, parallel-group study, 97 patients were evaluated for signs and symptoms of ocular infection or inflammation after bilateral LASIK. Group 1 (50 patients, 100 eyes) received a combined formulation of 0.3% gatifloxacin + 1% prednisolone acetate (Zypred®) plus placebo. Group 2 (47 patients, 94 eyes) received conventional treatment with the same agents from separate vials. The cohorts were similar in age, sex, race, and refractive error. Baseline and postoperative assessments were made on surgery days —2, 1, 3, and 15 and consisted of visual acuity; intraocular pressure; severity of inflammation of eyelids, conjunctiva, and cornea; tearing; ocular discomfort (foreign-body sensation, itching, or photophobia); and ocular pain. The posterior segment was evaluated at the screening and exit visits.Results: No ocular infection or persistent inflammation was detected in either group at any time. All objective and subjective criteria of efficacy were similar regardless of treatment, with no significant differences between the groups. More patients who were dosed with the combined agent complained of mild ocular discomfort on day 3, but this difference had disappeared by day 15.Conclusion: Post-LASIK topical prophylaxis with combined gatifloxacin + prednisolone eye drops (Zypred®) was well tolerated. This formulation appears to be therapeutically equivalent to conventional dosing with gatifloxacin and prednisolone from individual bottles for topical prophylaxis after laser refractive surgery.Keywords: gatifloxacin, prednisolone, LASIK, prophylaxis